Evidence that the Amyloid beta Precursor Protein-intracellular domain lowers the stress threshold of neurons and has a "regulated" transcriptional role - Giliberto, Luca; Zhou, Dawang; Weldon, Richard; Tamagno, Elena; De Luca, Pasquale; Tabaton, Massimo; D'Adamio, Luciano (Molecular Neurodegeneration, 2008)
Regulated intramembrane proteolysis of the β-amyloid precursor protein by the γ-secretase yields two peptides. One, amyloid-β, is the major component of the amyloid plaques found in Alzheimer's disease patients. The other, APP IntraCellular Domain, has been involved in regulation of apoptosis, calcium flux and gene transcription. To date, a few potential target genes transcriptionally controlled by AID, alone or complexed with Fe65/Tip60, have been described. Although the reports are controversial: these include KAI1, Neprilysin, p53, EGFR, LRP and APP itself. Furthermore, p53 has been implicated in AID mediated susceptibility to apoptosis. To extend these findings, and assess their in vivo relevance, we have analyzed the expression of the putative target genes and of the total brain basal transriptoma in transgenic mice expressing AID in the forebrain. Also, we have studied the susceptibility of primary neurons from such mice to stress and pro-apoptotic agents.